2006
DOI: 10.1002/masy.200651315
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Polyelectrolytes with Metal Ion Removal Ability by Using the Liquid Phase Based Retention Technique

Abstract: Summary: Water-soluble polyelectrolytes containing carboxylic acid groups were investigated as polychelatogens, in view to study their metal ion binding properties, using the liquid-phase polymer-based retention technique under different experimental conditions. The divalent metal ions investigated were: Co 2þ , Cu 2þ , Zn 2þ , and Cd 2þ . When the pH increased above 3, and especially at pH 5, metal ion retention capability increased as the majority of the functional groups are carboxylate, which can form more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The same behaviour has been reported in the case of the retention of cations such as Cd 2+ [29] by PEUF in presence of PANH4. It has been often reported that when interactions between water soluble polymers and metalions in solution take place by according bonds, the nature of the metal ions and the effect of pH may induce differences in the retention profiles and selectivity of equally charged metal ions [30].…”
Section: Effect Of Phsupporting
confidence: 83%
“…The same behaviour has been reported in the case of the retention of cations such as Cd 2+ [29] by PEUF in presence of PANH4. It has been often reported that when interactions between water soluble polymers and metalions in solution take place by according bonds, the nature of the metal ions and the effect of pH may induce differences in the retention profiles and selectivity of equally charged metal ions [30].…”
Section: Effect Of Phsupporting
confidence: 83%
“…It has been often reported that when interactions between water-soluble polymers and metal-ions in solution take place by according bonds, the nature of the metal-ions and the effect of pH may induce differences in the retention profiles and selectivityof equally charged metal-ions [33]. The carboxylic groups PAA are expected to exhibit unlike acid strengths.…”
Section: Effect Of Ph On the Removal Of CVmentioning
confidence: 99%
“…It is found that the aqueous soluble polycitramides have much higher metal chelating capabilities than the copolymers synthesized from citric acid and D ‐sorbitol 16. The new polymers can be used as a novel type of so‐called polychelatogens (soluble polymers as metal chelators)17–22 and detergent builders (water‐softeners) 23–25. This study provides a new route to incorporation of a renewable natural material into new ionic polymers 21, 26–28…”
Section: Introductionmentioning
confidence: 91%